Técnicas geoestatísticas na avaliação de atributos químicos em Cambissolo com agrofloresta e cana-de-açúcar em Humaitá, Amazonas - De Aquino, Renato Eleoterio [UNESP]; Campos, Milton César Costa; De Oliveira, Ivanildo Amorim [UNESP]; Siqueira, Diego Silva [UNESP]; Soares, Marcelo Dayron Rodrigues; De Freitas, Ludmila [UNESP] (Revista Brasileira de Ciencias Agrarias, 2015)
There is a lack of studies focusing on the spatial behavior of chemical attributes in the Amazon. In this sense, the objective of this study was to use geostatistical techniques in the evaluation of chemical attributes in agroforestry soil and sugarcane in Humaitá, Amazonas. The study was conducted in a rural property in Humaitá, Amazonas. These areas were established knitwear 70.00 mx 70.00 m, with regular spacing of 10.00 m totaling 64 points and then collected soil samples at a depth of 0.0 to 0.20 and 0.40 to 0.60 m. We determined the chemical attributes (pH, OM, P, K, Ca, Mg, SB, CTC, V% and H + Al). They used descriptive statistics and geostatistics which set individual and scaled semivariogram, and then estimated the sample density based on the achievement of semivariograms. The soil attributes presented spatial dependence structure mostly, predominantly moderate degree of spatial dependence, individual and staggered semivariograms. The sample density and spacing of the stepped semivariogram indicated fewer points and increased spacing to represent the areas of agroforestry and sugarcane.
Geostatistical techniques in the evaluation of chemical attributes in Cambisol with agroforestry and sugarcane in Humaita, Amazonas, Brazil
Keywords: Soil attributes; Southern Amazonas; Spatial variability